Motivasi Yang Dilaksanakan Oleh Penyedia Unit Pemasaran Bisnis Dalam Upaya Mencapai Efektivitas Penghimpunan Dana Tabungan Di PT. Bank XYZ Kantor Cabang ( Periode September S/D Desember 1996) - Harijadi, Dadi (Sekolah Tinggi Ilmu Ekonomi Kesatuan, 2001)
An effective collection of saving fund is necessarily important to most banks for it is one of the aims to achieve maximum profit. It takes motivational aspects from the unit leader that must be carried out by the business marketing unit supervisor.